Controllable Selenization Transformation from MoO2 to MoSe2 by Gas Pressure‐Mediated Chemical Vapor Deposition. Issue 14 (8th June 2022) - Shen, Chengtao; Tian, Feng; Qiu, Peng; He, Yingfeng; Wei, Huiyun; Song, Yimeng; Li, Ye; Liu, Heng; Zhu, Xiaoli; Zheng, Xinhe; Peng, Mingzeng
Abstract : During the chemical vapor deposition (CVD) of MoSe2, controlling its selenization reaction and understanding its reaction mechanisms are of great significance to obtain high‐quality 2D transition metal selenide semiconductors. Herein, a variable‐pressure CVD (VPCVD) method is reported to achieve the controllable transformation from MoO2 to MoSe2 monolayer based on gas pressure‐mediated selenization. At the gas pressure lower than 20 KPa, high‐temperature decomposition of MoO3 in the Ar/H2 mixture only produces MoO2 nanosheets without any selenization. When the gas pressure is between 20 and 60 KPa, quadrilateral MoO2 nanosheets are partially selenized. By further increasing the gas pressure from 60 to 100 KPa, they are completely selenized. At the downstream margins of as‐selenized films, 2D MoSe2 monolayers demonstrate a morphological evolution from triangle to hexagon and then to a continuous film. In addition, their Se vacancy concentrations and nucleation sizes depend directly on gas pressure. Therefore, the gas pressure‐mediated selenization provides a feasible way for the in situ synthetic control of chemical composition and vacancy doping of 2D transition metal selenides/oxides. Abstract : Gas pressure‐mediated selenization provides a feasible way for the in situ synthetic control of chemical composition and vacancy doping of 2D transition metal selenides/oxides.